2010
DOI: 10.1105/tpc.109.072827
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analyses of Caffeic Acid O-Methyltransferase and Cinnamoyl-CoA-Reductase Genes from Perennial Ryegrass (Lolium perenne)

Abstract: Cinnamoyl CoA-reductase (CCR) and caffeic acid O-methyltransferase (COMT) catalyze key steps in the biosynthesis of monolignols, which serve as building blocks in the formation of plant lignin. We identified candidate genes encoding these two enzymes in perennial ryegrass (Lolium perenne) and show that the spatio-temporal expression patterns of these genes in planta correlate well with the developmental profile of lignin deposition. Downregulation of CCR1 and caffeic acid O-methyltransferase 1 (OMT1 ) using an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
128
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(140 citation statements)
references
References 83 publications
8
128
1
1
Order By: Relevance
“…These compounds were identified mainly as kaempferol glycosides (Table 2), which occur in many plants (Chopin and Dellamonica, 1988). Tu et al (2010), recently identified several flavonols in L. perenne, including some of the compounds identified in the present study, that is, kaempferol-3-O-rutinoside, rutin and kaempferol-3-O-glucosyl-rhamnosyl-galactoside. However, these authors did not report the presence of kaempferol, kaempferol-O-acetyl-glucoside and kaempferol-xylosyl-rhamnoside found in the present study (Table 2).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…These compounds were identified mainly as kaempferol glycosides (Table 2), which occur in many plants (Chopin and Dellamonica, 1988). Tu et al (2010), recently identified several flavonols in L. perenne, including some of the compounds identified in the present study, that is, kaempferol-3-O-rutinoside, rutin and kaempferol-3-O-glucosyl-rhamnosyl-galactoside. However, these authors did not report the presence of kaempferol, kaempferol-O-acetyl-glucoside and kaempferol-xylosyl-rhamnoside found in the present study (Table 2).…”
Section: Discussionsupporting
confidence: 54%
“…There is surprisingly little information available on the polyphenols that are present in this plant. Several studies analysed simple phenolic acids in ryegrass Jones, 1976, 1977) and two recent reports also described the presence of flavonoids (Tu et al, 2010;Qawasmeh et al, 2012). As plants belonging to the Poaceae family appear to have a narrower range of polyphenolic compounds than plants belonging to the Fabaceae family (Harborne, 1967; Although not confirmed by other means, it is likely that the flavonols are glycosylated at carbon 3.…”
Section: Discussionmentioning
confidence: 99%
“…This might have been due to the difference in the plant internodes/segments used for analytical pyrolysis and histochemical analysis. Maüle staining and acetyl bromide-soluble lignin content of the downregulated OMT and CCR in transgenic perennial ryegrass plants showed different lignin content and S/G ratio in different internodes of the same transgenic plant (Tu et al, 2010).…”
Section: Sl Pang Et Almentioning
confidence: 99%
“…Lignin content increases with progressive maturity of stems; these relationships have been studied in detail in alfalfa (Jung et al, 1997;Chen et al, 2006), ryegrass (Tu et al, 2010), tall fescue (Buxton & Redfearn 1997;Chen et al, 2002) and switchgrass (Mann et al, 2009;Shen et al, 2009). Decreasing the lignin content increases the digestibility of alfalfa for ruminant animals (Baucher et al, 1999; Guo et al, 2001a,b;Reddy et al, 2005) 4 and improves processing efficiency for production of liquid biofuels through saccharification and fermentation .…”
Section: Function and Distribution Of Lignin In Plantsmentioning
confidence: 99%
“…A correlation has been shown between degradability of the cell walls in forages and the amount of G lignin, as lignin rich in G units is more highly condensed, making it less amenable to degradation (Jung & Deetz 1993). Thus, transgenic poplar plants with lignin rich in G units are, like softwoods, more difficult to pulp because of their more condensed lignin (Lapierre et al, 1999).Lignin content increases with progressive maturity of stems; these relationships have been studied in detail in alfalfa (Jung et al, 1997;Chen et al, 2006), ryegrass (Tu et al, 2010), tall fescue (Buxton & Redfearn 1997;Chen et al, 2002) and switchgrass (Mann et al, 2009;Shen et al, 2009). Decreasing the lignin content increases the digestibility of alfalfa for ruminant animals (Baucher et al, 1999; Guo et al, 2001a,b;Reddy et al, 2005) 4 and improves processing efficiency for production of liquid biofuels through saccharification and fermentation .…”
mentioning
confidence: 99%